2017
DOI: 10.3390/nu9030226
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient‐Fortified Milk and Academic  Performance among Chinese Middle School Students:  A Cluster‐Randomized Controlled Trial

Abstract: Many children suffer from nutritional deficiencies that may negatively affect their academic performance. This cluster-randomized controlled trial aimed to test the effects of micronutrient-fortified milk in Chinese students. Participants received either micronutrient-fortified (n = 177) or unfortified (n = 183) milk for six months. Academic performance, motivation, and learning strategies were estimated by end-of-term tests and the Motivated Strategies for Learning Questionnaire. Blood samples were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Of note is that many countries promote both water and cow's milk as healthy beverages, and these may be competing for messaging space. Especially in settings where malnutrition is a major public health concern, (fortified) cow's milk can contribute important nutrients to a child's diet . Although guidelines mainly recommend including skim or low‐fat milk as part of children's diet, recent observational evidence points towards a negative association between milk fat percentage and children's body mass index (BMI) .…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that many countries promote both water and cow's milk as healthy beverages, and these may be competing for messaging space. Especially in settings where malnutrition is a major public health concern, (fortified) cow's milk can contribute important nutrients to a child's diet . Although guidelines mainly recommend including skim or low‐fat milk as part of children's diet, recent observational evidence points towards a negative association between milk fat percentage and children's body mass index (BMI) .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, most of the studies had a low RoB for randomization and an unclear RoB for allocation concealment because none of the RCTs adequately reported on the methods used for allocation concealment. Four studies had a high RoB for blinding because of lack of blinding [43][44][45][46]. One study had a moderate RoB for incomplete outcome data because the author did perprotocol analysis that led to the exclusion of 20% of children that were participating in an arm not relevant to the analysis group [47].…”
Section: Rob In the Included Studiesmentioning
confidence: 99%
“…Two studies reported on school performances in math, science, and social science [44,54]. Academic performance was measured using age-and gender-standardized end-of-term test scores retrieved from the school administration system.…”
Section: School Performance and Absencesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that deficiency of micronutrients, especially such as zinc, chromium, selenium and others, today there is an acute issue [2,5,7,15,16,17,18]. The deficiency of microelements reduces the body's resistance to various diseases, accelerates the aging process, increases the negative impact of adverse environmental conditions, and prevents the formation of a healthy generation [6,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%